Analysis of Sharia-Based Governance in The Takaful Industry: A Review of Contemporary Literature - Muhammad Arifin Lubis; Asmaul Husna; Sella Kurnia Sari; Fauziah Hanum (Economics and Business Journal (ECBIS), 2026)
This study aims to explore and evaluate the development of studies on shariah-based governance in the takaful industry through a systematic literature review approach. Sharia governance has an important role in ensuring that all processes, policies, and operational activities of takaful companies are implemented in accordance with sharia regulations, while supporting the principles of transparency, accountability, fairness, and protection of participants' rights. This study uses the Systematic Literature Review (SLR) method by adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The databases used are Scopus and Google Scholar with the keywords "Shariah Governance", "Islamic Governance", "Takaful Industry", "Takaful Governance", and "Shariah Governance in Takaful". Through the process of identification, screening, and feasibility assessment, 7 articles that meet the inclusion criteria were obtained for thematic analysis. The results of the study show that the effectiveness of sharia governance in the takaful industry is determined by five main elements: the role and competence of the Sharia Supervisory Board (DPS), the sharia compliance and audit system, the corporate governance mechanism, the transparency of information disclosure based on AAOIFI standards, and the support of the regulatory framework. This research provides theoretical contributions to the development of the concept of sharia governance in the Islamic insurance industry as well as practical recommendations for regulators, takaful operators, and Sharia Supervisory Boards.